Hot-melt adhesive composition, pre-coating skin material for automotive interior, automotive interior material, and method for producing bonded body

By using a hot melt adhesive composition of a specific composition, the problems of adhesion and component migration of pre-coated skin materials in summer temperature and humidity environments are solved, and crack resistance is maintained during transportation, suitable for automotive interior materials.

CN119410302APending Publication Date: 2025-02-11SUNSTAR GIKEN KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411744930.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-10-03
Filing Date
2024-11-29
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

In summer temperature and humidity environments, pre-coated skin materials stored in a laminated state are prone to adhesion and migration of hot melt adhesive components, and crack problems are prone to occur during transportation.

Method used

Using a hot melt adhesive composition comprising an alpha-olefin copolymer made using a single center catalyst, an ethylene-polar group-containing monomer copolymer and a polypropylene wax, and through a specific Mix proportionally to improve adhesion and heat resistance.

Benefits of technology

The hot melt adhesive composition significantly improves the adhesion resistance and component migration resistance of the pre-coated skin material in the laminated state, and maintains crack resistance during transportation. It is suitable for pre-coated skin material for automotive interiors and Car interior materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005163482320000301
    Figure BDA0005163482320000301
  • Figure BDA0005163482320000311
    Figure BDA0005163482320000311
  • Figure BDA0005163482320000321
    Figure BDA0005163482320000321
Patent Text Reader

Abstract

The invention provides a hot melt adhesive which has good adhesion and heat resistance, excellent blocking resistance and component migration resistance, and excellent crack resistance during transportation. A hot melt adhesive composition comprising: an alpha-olefin (co) polymer (A) having a Shore A hardness of 80 or more and produced using a single-site catalyst; an alpha-olefin (co) polymer (B) having a Shore A hardness of less than 80, made using a single site catalyst; an ethylene-polar group-containing monomer copolymer (C); and a polypropylene wax (D); the content of (D) is 60-300 parts by mass per 100 parts by mass of the total of (A), (B), and (C).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a hot melt adhesive composition, a pre-coated surface material for automobile interior using the hot melt adhesive composition, and an automobile interior material. Background Art

[0002] Hot melt adhesives are solid at room temperature, and are applied to substrates after being heated and melted, and then solidified by cooling to bond the substrates together. Hot melt adhesives are solvent-free, and compared with solvent-based adhesives, they have advantages such as reduced VOC (volatile organic compounds) and increased productivity due to the omission of the drying process, and can be used for various purposes, such as automobile manufacturing.

[0003] Door trims, instrument panels, ceiling materials, rear trays, pillars, etc., which are automotive interior materials, are generally composed of molded products and surface materials. Molded products mainly use polyolefin molded products and ABS molded products. On the other hand, the surface materials use soft polyvinyl chloride artificial leather with polyolefin foam, olefin thermoplastic elastomer artificial leather with polyolefin foam, fabric with polyurethane foam, and other surface materials. These molded products and surface materials are bonded via adhesives by vacuum forming, compression molding, and the like.

[0004] Patent document 1 discloses a pre-coated surface material for automobile interior, characterized in that a hot-melt adhesive is pre-coated on the back side of the automobile interior surface material, the hot-melt adhesive comprising as essential components an amorphous poly(α-olefin) (A) having a melt viscosity in the range of 500 mPa·s / 190°C to 100,000 mPa·s / 190°C, a binder resin (B) having a softening point of 110°C or higher as measured by a ring and ball method, and a polypropylene wax (C) having a melting point of 120°C or higher, and the weight ratio of (A) to (C) is 100 / 50 to 100 / 100.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2004-284575 Summary of the invention

[0008] Problems to be solved by the invention

[0009] When using hot melt adhesives, depending on the process, a process (for example, vacuum forming process) is required to temporarily store the surface material (pre-coated surface material) coated with the hot melt adhesive. Pre-coated surface materials are mostly handled in the form of single sheets and stored in a stacked state. For existing hot melt adhesives, when the pre-coated surface materials are stored in a stacked state under the temperature and humidity environment of summer, problems such as adhesion between the pre-coated surface materials and migration of part of the hot melt adhesive components to the surface material side may occur. Although adhesion and component migration can be improved by sandwiching release paper and release film between the pre-coated surface materials, problems will arise from the perspective of cost and operability. In addition, existing hot melt adhesives may have the problem of cracking due to impact or vibration during transportation.

[0010] Patent document 1 mentions: providing a pre-coated surface material for automobile interior materials, which is made of a non-adhesive adhesive with no stickiness and excellent durability and adhesive properties, and a method for manufacturing an automobile interior material; providing a pre-coated surface material for automobile interior materials, which has good adhesion to olefin materials, shows excellent heat resistance, and is a solvent-free type, and a method for manufacturing an automobile interior material, etc. (refer to patent document 1

[0013] to

[0015] , etc.).

[0011] However, Patent Document 1 has not actually studied the blocking resistance of the pre-coating skin material when it is stored in a stacked state, and is unclear. Furthermore, the component migration resistance of the pre-coating skin material when it is stored in a stacked state and the crack resistance during transportation are also unclear.

[0012] The object of the present disclosure is to provide a hot melt adhesive having good adhesion and heat resistance to resin substrates, particularly polyolefin substrates represented by polypropylene, and having excellent blocking resistance and component migration resistance when pre-coated skin materials are stored in a stacked state, and excellent crack resistance during transportation.

[0013] Technical means to solve problems

[0014] The inventors of the present invention have repeatedly conducted in-depth research and found that a hot melt adhesive composition is obtained, which contains a specific α-olefin (co)polymer (A), another specific α-olefin (co)polymer (B), an ethylene-polar group-containing monomer copolymer (C), and a polypropylene wax (D), and contains a specific amount of (D) relative to 100 parts by mass of (A) to (C). This hot melt adhesive composition has good adhesion and heat resistance, and even if the pre-coated surface material is stored in a stacked state, it has excellent resistance to blocking and component migration, and excellent crack resistance during transportation, and is suitable for use in pre-coated surface materials for automobile interiors and automobile interior materials, thereby completing the present invention.

[0015] This specification includes the following embodiments.

[0016] [Item 1]

[0017] A hot melt adhesive composition comprising:

[0018] An α-olefin (co)polymer (A) having a Shore A hardness of 80 or more produced using a single-site catalyst;

[0019] α-olefin (co)polymers (B) having a Shore A hardness of less than 80 produced using a single-site catalyst;

[0020] an ethylene-polar group-containing monomer copolymer (C); and

[0021] Polypropylene wax (D);

[0022] The polypropylene wax (D) contains more than 60 parts by mass and less than 300 parts by mass relative to 100 parts by mass of the total amount of the α-olefin (co)polymer (A), the α-olefin (co)polymer (B) and the ethylene-polar group-containing monomer copolymer (C).

[0023] [Item 2]

[0024] The hot-melt adhesive composition according to item 1, wherein the α-olefin (co)polymer (A) comprises at least one selected from the group consisting of polypropylene, ethylene-propylene copolymers and propylene-butene copolymers.

[0025] [Item 3]

[0026] The hot-melt adhesive composition according to item 1 or 2, wherein a part of the copolymerization component of the α-olefin (co)polymer (B) contains a repeating unit derived from propylene.

[0027] [Item 4]

[0028] The hot-melt adhesive composition according to any one of items 1 to 3, wherein the ethylene-polar group-containing monomer copolymer (C) comprises at least one selected from the group consisting of ethylene-vinyl acetate copolymers and ethylene-ethyl acrylate copolymers.

[0029] [Item 5]

[0030] The hot-melt-adhesive composition according to any one of items 1 to 4, wherein the polypropylene wax (D) has a softening point of 90° C. or higher.

[0031] [Item 6]

[0032] The hot-melt-adhesive composition according to any one of Items 1 to 5, comprising a binder (E).

[0033] [Item 7]

[0034] The hot-melt adhesive composition according to item 6, wherein the binder (E) comprises at least one selected from the group consisting of hydrogenated petroleum resins, terpene resins, and hydrogenated terpene phenolic resins.

[0035] [Item 8]

[0036] The hot-melt-adhesive composition according to any one of Items 1 to 7, further comprising an antioxidant (F).

[0037] [Item 9]

[0038] The hot-melt adhesive composition according to any one of items 1 to 8, wherein the melt viscosity at 180° C. is 10,000 mPa·s or more and 50,000 mPa·s or less.

[0039] [Item 10]

[0040] The hot-melt adhesive composition according to any one of Items 1 to 9, which is used for an automobile interior material.

[0041] [Item 11]

[0042] A pre-coated surface material for automobile interior, comprising: a surface material for automobile interior, and a hot-melt adhesive layer formed of the hot-melt adhesive composition according to any one of items 1 to 10 on the back side of the surface material for automobile interior.

[0043] [Item 12]

[0044] An automobile interior material, comprising an automobile interior molded article and the automobile interior pre-coat skin material according to item 11, wherein the automobile interior pre-coat skin material is bonded to the automobile molded article via the hot-melt adhesive layer.

[0045] [Item 13]

[0046] A method for manufacturing an adhesive body, wherein:

[0047] The adhesive body comprises a first substrate and a second substrate, wherein the second substrate is bonded to the first substrate via a hot-melt adhesive layer formed from the hot-melt adhesive composition according to any one of items 1 to 10.

[0048] The method for producing an adhesive body comprises the step of bringing a mold into contact with the hot-melt adhesive composition.

[0049] [Item 14]

[0050] A method for producing a hot melt adhesive composition, comprising:

[0051] Preparation: an α-olefin (co)polymer (A) having a Shore A hardness of 80 or more produced using a single-site catalyst, an α-olefin (co)polymer (B) having a Shore A hardness of less than 80 produced using a single-site catalyst, an ethylene-polar group-containing monomer copolymer (C), and a polypropylene wax (D);

[0052] Relative to 100 parts by mass of the total amount of the above-mentioned α-olefin (co)polymer (A), the above-mentioned α-olefin (co)polymer (B) and the ethylene-polar group-containing monomer copolymer (C), 60 parts by mass or more and 300 parts by mass or less of the above-mentioned polypropylene wax (D) are melt-mixed.

[0053] [Effects of the invention]

[0054] The hot-melt adhesive composition of the present invention has excellent adhesion and heat resistance, and even when the pre-coated surface material coated with the hot-melt adhesive composition is stored in a laminated state, it has excellent blocking resistance and component migration resistance, and excellent crack resistance during transportation. Therefore, it can be used to manufacture pre-coated surface materials for automobile interiors, automobile interior materials, etc. DETAILED DESCRIPTION

[0055] <Hot-melt adhesive composition>

[0056] The hot melt adhesive composition of the present invention comprises: an α-olefin (co)polymer (A) having a Shore A hardness of 80 or more produced using a single-site catalyst, an α-olefin (co)polymer (B) having a Shore A hardness of less than 80 produced using a single-site catalyst, an ethylene-polar group-containing monomer copolymer (C), and a polypropylene wax (D). In addition to the components (A) to (D), the hot melt adhesive composition of the present invention may further comprise one or more selected from a binder (E), an antioxidant (F), an inorganic filler (G), a plasticizer (H), other additives, etc., as required.

[0057] [(A) α-olefin (co)polymer having a Shore A hardness of 80 or more produced using a single-site catalyst]

[0058] The hot melt adhesive composition disclosed herein contains an α-olefin (co)polymer (A) (also referred to as component (A), α-olefin (co)polymer (A)) having a Shore A hardness of 80 or more produced using a single-site catalyst. The above-mentioned α-olefin (co)polymer (A) is a polyolefin having crystallinity produced using a single-site catalyst. From the viewpoints of crystallinity, Shore A hardness and / or molecular weight, the above-mentioned α-olefin (co)polymer (A) is a substance that is different from the other components described in this specification. Typically, the crystallinity of the above-mentioned α-olefin (co)polymer (A) is 20% or more. Typically, the Shore A hardness of the above-mentioned α-olefin (co)polymer (A) is 80 or more. Typically, the weight average molecular weight of the above-mentioned α-olefin (co)polymer (A) is 40,000 or more.

[0059] The crystallinity of the above-mentioned α-olefin (co)polymer (A) may be 20% or more, 25% or more, 30% or more, or 35% or more. The crystallinity of the above-mentioned α-olefin (co)polymer (A) may be 100% or less, 98% or less, 95% or less, 90% or less, or 85% or less. From the viewpoint of better exerting the effect of the present disclosure, it is appropriate for the crystallinity to be above the above lower limit. The crystallinity can be measured, for example, by differential scanning calorimetry. It should be noted that "crystallinity" in the present disclosure may refer to the property of observing a clear endothermic peak originating from the crystalline part in the differential scanning calorimetry, and on the other hand, "amorphous" may refer to the property of not observing a clear endothermic peak originating from the crystalline part in the differential scanning calorimetry.

[0060] The Shore A hardness of the above-mentioned α-olefin (co)polymer (A) can be 80 or more, 85 or more, 90 or more, 95 or more, preferably 80 or more. The Shore A hardness of the above-mentioned α-olefin (co)polymer (A) can be 100 or less, 99 or less, 98 or less, or 97 or less. The Shore A hardness can be used as an indicator of resin cohesion, and can be used as one of the indicators of room temperature adhesion and thermal adhesion. From the viewpoint of better exerting the effect of the present disclosure, it is appropriate for the Shore A hardness of the α-olefin (co)polymer (A) to be within the above-mentioned range. The Shore A hardness of the α-olefin (co)polymer (A) can be measured according to the method described in JIS K6253-3:2012 (Vulcanized rubber and thermoplastic rubber-Method for determining hardness).

[0061] The melting point of the above-mentioned α-olefin (co)polymer (A) may be 80°C or more, 90°C or more, 100°C or more or 110°C or more, preferably 80°C or more. The melting point of the above-mentioned α-olefin (co)polymer (A) may be 150°C or less, 140°C or less, 130°C or less, 120°C or less, 110°C or less, 100°C or less or 90°C or less, preferably 130°C or less. From the viewpoint of better exerting the effects of the present disclosure, it is appropriate that the melting point of the α-olefin (co)polymer (A) is within the above-mentioned range. The melting point of the α-olefin (co)polymer (A) can be measured according to the method described in JIS K7121:2012 (Method for Determining Transition Temperature of Plastics).

[0062] The glass transition temperature of the α-olefin (co)polymer (A) may be -150°C or higher, -125°C or higher, -100°C or higher, -75°C or higher, -50°C or higher, or -25°C or higher. The glass transition temperature of the α-olefin (co)polymer (A) may be 20°C or lower, 10°C or lower, 0°C or lower, -10°C or lower, or -20°C or lower, preferably 0°C or lower, and more preferably -10°C or lower. From the viewpoint of low-temperature adhesion, the glass transition temperature is preferably below the above upper limit. The glass transition temperature of the α-olefin (co)polymer (A) can be measured according to the method described in JIS K7121:2012 (Method for determining transition temperature of plastics).

[0063] The above-mentioned α-olefin (co)polymer (A) is typically thermoplastic. The MFR of the above-mentioned α-olefin (co)polymer (A) can be 3g / 10 minutes or more, 5g / 10 minutes or more, 7g / 10 minutes or more, 10g / 10 minutes or more, 12g / 10 minutes or more, or 15g / 10 minutes or more, preferably 5g / 10 minutes or more, and more preferably 7g / 10 minutes or more. The MFR of the above-mentioned α-olefin (co)polymer (A) can be 40g / 10 minutes or less, 30g / 10 minutes or less, 20g / 10 minutes or less, 15g / 10 minutes or less, or 10g / 10 minutes or less. From the viewpoint of low melt viscosity and coating stability, it is preferred that the MFR is within the range above the above lower limit. MFR can be measured based on JIS K7210.

[0064] The weight average molecular weight of the α-olefin (co)polymer (A) may be 40,000 or more, 50,000 or more, 75,000 or more, 100,000 or more, 200,000 or more, 300,000 or more, or 500,000 or more, preferably 100,000 or more. The weight average molecular weight of the α-olefin (co)polymer (A) may be 5,000,000 or less, 2,000,000 or less, 1,500,000 or less, 1,200,000 or less, 1,000,000 or less, 800,000 or less, 600,000 or less, 400,000 or less, or 200,000 or less, preferably 1,000,000 or less, for example, 600,000 or less. From the viewpoint of better exerting the effects of the present disclosure, it is appropriate that the weight average molecular weight is within the above range. The weight average molecular weight of the α-olefin (co)polymer (A) can be measured according to the method described in JIS K7252-1:2016 (Plastics - Method for determining average molecular weight and molecular weight distribution of polymers by size exclusion chromatography).

[0065] The α-olefin (co)polymer (A) is a polymer having repeating units derived from olefins. The α-olefin (co)polymer (A) may be a homopolymer, a copolymer or a mixture thereof. The copolymer may be in the form of a random copolymer, a block copolymer, a graft copolymer or the like.

[0066] Examples of repeating units contained in the above-mentioned α-olefin (co)polymer (A) include, for example, repeating units derived from ethylene, propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, and 1-eicosene, and these repeating units may be contained alone or in combination of two or more thereof.

[0067] The α-olefin (co)polymer (A) preferably includes repeating units derived from propylene among the repeating units, and may include, for example, repeating units derived from propylene and repeating units derived from other α-olefins (e.g., ethylene). Among the repeating units constituting the α-olefin (co)polymer (A), the repeating units derived from propylene may account for 20 mol% or more, 30 mol% or more, 40 mol% or more, 50 mol% or more, 60 mol% or more, or 70 mol% or more, and preferably 30 mol% or more.

[0068] The α-olefin (co)polymer (A) is produced by polymerizing α-olefin using a single-site catalyst. Compared with α-olefin (co)polymers polymerized using a multi-site catalyst, the α-olefin (co)polymers polymerized using a single-site catalyst have a uniform molecular weight distribution and a uniform crystallinity distribution, and contain fewer low molecular weight components, so the viscosity is smaller, which is preferred from the viewpoint of anti-blocking properties.

[0069] Specific examples of the α-olefin (co)polymer (A) include copolymers of olefins such as ethylene homopolymers, propylene homopolymers, 1-butene homopolymers, ethylene-propylene copolymers, propylene-1-butene copolymers, ethylene-1-octene copolymers, ethylene-1-hexene copolymers, and ethylene-propylene-1-butene copolymers, and preferred examples include propylene homopolymers, ethylene-propylene copolymers, and propylene-1-butene copolymers. These α-olefin (co)polymers (A) may be used alone or in combination of two or more.

[0070] Representative commercial products of the α-olefin (co)polymer (A) include: WINTEC series manufactured by Japan Polypro with trade names such as “WINTEC WMX03”, “WINTEC WSX03”, and “WINTEC WSX03A”; L-MODU series manufactured by Idemitsu Kosan with trade names such as “L-MODU S901”, “L-MODU S600”, and “L-MODU S400”; TAFMER series manufactured by Mitsui Chemicals with trade names such as “TAFMER XM-7090”, “TAFMER XM-7080”, “TAFMER XM-7070”, “TAFMER XM-5090”, “TAFMER XM-5080”, “TAFMER XM-5070”, “TAFMER BL-2491M”, and “TAFMERDF110”; VERSIFY series manufactured by Dow Chemical with trade names such as “VERSIFY 3000” and “VERSIFY 4200”; Vistamaxx series such as "Vistamaxx 8880", "Vistamaxx 3588FL", and "Vistamaxx 3980FL" manufactured by Mobil Corporation, etc. The α-olefin (co)polymer (A) may be used alone or in combination of two or more.

[0071] [(B) α-olefin (co)polymers having a Shore A hardness of less than 80 produced using a single-site catalyst]

[0072] The hot melt adhesive composition disclosed herein comprises an α-olefin (co)polymer (B) (also referred to as component (B), α-olefin (co)polymer (B)) having a Shore A hardness of less than 80 produced using a single-site catalyst. The above-mentioned α-olefin (co)polymer (B) is a polyolefin having a melting point and can impart flexibility. From the viewpoints of crystallinity and / or molecular weight, the above-mentioned α-olefin (co)polymer (B) is a substance that is different from the other components described in this specification. Typically, the above-mentioned α-olefin (co)polymer (B) is not amorphous. Typically, the Shore A hardness of the above-mentioned α-olefin (co)polymer (B) is less than 80. Typically, the weight average molecular weight of the above-mentioned α-olefin (co)polymer (B) is 40,000 or more.

[0073] The Shore A hardness of the α-olefin (co)polymer (B) may be 20 or more, 30 or more, 40 or more, 50 or more, 60 or more, or 70 or more, preferably 40 or more. The Shore A hardness of the α-olefin (co)polymer (B) may be less than 80, less than 75, less than 70, less than 65, or less than 60. From the viewpoint of better exerting the effects of the present disclosure, it is appropriate that the Shore A hardness of the α-olefin (co)polymer (B) is within the above range. The Shore A hardness of the α-olefin (co)polymer (B) can be measured according to the method described in component (A).

[0074] The above-mentioned α-olefin (co)polymer (B) is typically thermoplastic. The MFR of the above-mentioned α-olefin (co)polymer (B) can be 3g / 10 minutes or more, 5g / 10 minutes or more, 7g / 10 minutes or more, 10g / 10 minutes or more, 12g / 10 minutes or more, or 15g / 10 minutes or more, preferably 5g / 10 minutes or more, and more preferably 7g / 10 minutes or more. The MFR of the above-mentioned α-olefin (co)polymer (B) can be 40g / 10 minutes or less, 30g / 10 minutes or less, 20g / 10 minutes or less, 15g / 10 minutes or less, or 10g / 10 minutes or less. From the viewpoint of low melt viscosity and coating stability, it is preferred that the MFR is within the range above the above lower limit. MFR can be measured based on JIS K7210.

[0075] The weight average molecular weight of the α-olefin (co)polymer (B) may be 40,000 or more, 50,000 or more, 75,000 or more, 100,000 or more, 200,000 or more, 300,000 or more, or 500,000 or more, preferably 100,000 or more. The weight average molecular weight of the α-olefin (co)polymer (B) may be 5,000,000 or less, 2,000,000 or less, 1,500,000 or less, 1,200,000 or less, 1,000,000 or less, 800,000 or less, 600,000 or less, 400,000 or less, or 200,000 or less, preferably 1,000,000 or less, for example, 600,000 or less. From the viewpoint of better exerting the effects of the present disclosure, it is appropriate that the weight average molecular weight is within the above range. The weight average molecular weight of the α-olefin (co)polymer (B) can be measured according to the method described in the component (A).

[0076] The α-olefin (co)polymer (B) is a polymer having repeating units derived from olefins. The α-olefin (co)polymer (B) may be a homopolymer, a copolymer or a mixture thereof. The form of the (co)polymer may be any one of random copolymerization, block copolymerization, graft copolymerization, etc.

[0077] Examples of repeating units contained in the above-mentioned α-olefin (co)polymer (B) include, for example, repeating units derived from ethylene, propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, and 1-eicosene, and these repeating units may be contained alone or in combination of two or more thereof.

[0078] The α-olefin (co)polymer (B) preferably includes repeating units derived from propylene among the repeating units, and may include, for example, repeating units derived from propylene and repeating units derived from other α-olefins (e.g., ethylene). Among the repeating units constituting the α-olefin (co)polymer (B), the repeating units derived from propylene may account for 20 mol% or more, 30 mol% or more, 40 mol% or more, 50 mol% or more, 60 mol% or more, or 70 mol% or more, and preferably 30 mol% or more.

[0079] The α-olefin (co)polymer (B) is produced by polymerizing α-olefin using a single-site catalyst. Compared with α-olefin (co)polymers polymerized using a multi-site catalyst, the α-olefin (co)polymers polymerized using a single-site catalyst have a uniform molecular weight distribution and a uniform crystallinity distribution, and contain fewer low molecular weight components, so the viscosity is smaller, which is preferred from the viewpoint of anti-blocking properties.

[0080] Specific examples of the α-olefin (co)polymer (B) include copolymers of olefins such as ethylene homopolymers, propylene homopolymers, 1-butene homopolymers, ethylene-propylene copolymers, propylene-1-butene copolymers, ethylene-1-octene copolymers, ethylene-1-hexene copolymers, and ethylene-propylene-1-butene copolymers, and preferred examples include ethylene-propylene copolymers and propylene-1-butene copolymers. These α-olefin (co)polymers (B) may be used alone or in combination of two or more.

[0081] Examples of representative commercial products of the α-olefin (co)polymer (B) include: TAFMER PN series such as "TAFMER PN-2070" and "TAFMER PN-3560" manufactured by Mitsui Chemicals; INFUSE series such as "INFUSE 9807", "INFUSE 9817" and "INFUSE 9990" manufactured by Dow Chemical; Vistamaxx series such as "Vistamaxx 6502" and "Vistamaxx 6202" manufactured by Exxon Mobil, etc. It should be noted that the α-olefin (co)polymer (B) may be used alone or in combination of two or more thereof.

[0082] [(C) Ethylene-Polar Group-Containing Monomer Copolymer]

[0083] The hot melt adhesive composition of the present disclosure contains an ethylene-polar group-containing monomer copolymer (C) (also referred to as component (C) or copolymer (C). The ethylene-polar group-containing monomer copolymer (C) has repeating units derived from ethylene and a polar group-containing monomer. Specific examples of the polar group-containing monomer include carboxylic acid vinyl esters such as vinyl acetate, (meth)acrylic acid alkyl esters such as ethyl acrylate, and the like.

[0084] The copolymerization amount of the monomer containing the polar group may be 10% by mass or more, 20% by mass or more, preferably 10% by mass or more. The copolymerization amount of the monomer containing the polar group may be 50% by mass or less, 40% by mass or less, 30% by mass or less, preferably 30% by mass or less. From the viewpoint of better exerting the effect of the present disclosure, it is appropriate that the copolymerization amount of the monomer containing the polar group is within the above range.

[0085] The melting point of the ethylene-polar group-containing monomer copolymer (C) may be 50°C or more, 60°C or more, 70°C or more, 80°C or more, or 90°C or more, preferably 50°C or more. The melting point of the ethylene-polar group-containing monomer copolymer (C) may be 150°C or less, 140°C or less, 130°C or less, 120°C or less, 110°C or less, or 100°C or less, preferably 100°C or less. From the viewpoint of better exerting the effects of the present disclosure, it is appropriate that the melting point of the ethylene-polar group-containing monomer copolymer (C) is within the above range. The melting point of the ethylene-polar group-containing monomer copolymer (C) can be measured according to the method described in JIS K7121:2012 (Method for determining transition temperature of plastics).

[0086] Specific examples of the ethylene-polar group-containing monomer copolymer (C) include ethylene-vinyl acetate copolymers, ethylene-ethyl acrylate copolymers, etc. These copolymers (C) may be used alone or in combination of two or more.

[0087] Representative commercial products of the ethylene-polar group-containing monomer copolymer (C) include: Ultrathene series manufactured by Tosoh Corporation with the trade names of "Ultrathene 680", "Ultrathene 681", "Ultrathene 684", "Ultrathene 685", "Ultrathene 710", "Ultrathene 720", "Ultrathene 722", "Ultrathene 725", "Ultrathene 735", etc.; Evaflex series manufactured by Dow Mitsui Polychemicals with the trade names of "Evaflex EV210", "Evaflex EV220", "Evaflex EV310", "Evaflex EV410", "Evaflex EV420", "Evaflex EV450", etc.; ENEOS Ethylene-vinyl acetate copolymers with trade names such as "NUC-3830", "NUC-3461", and "NUC-3810" manufactured by NUC; "REXPEARLA6200" REXPEARL series manufactured by Japan Polyethylene; Ethylene-ethyl acrylate copolymers with trade names such as "NUC-6570", "NUC-6070", and "NUC-6940" manufactured by ENEOS NUC, etc.

[0088] [(D) Polypropylene wax]

[0089] The hot melt adhesive composition of the present disclosure contains a polypropylene wax (D) (also referred to as component (D)). The polypropylene wax (D) refers to a wax having a repeating unit derived from propylene. The polypropylene wax (D) is generally low molecular weight (weight average molecular weight less than 40,000), and can impart coating properties or wettability to an adherend by reducing the viscosity of the hot melt adhesive. In addition, the polypropylene wax (D) can increase the crystallinity of the α-olefin (co)polymer (A) and (B), increase the softening point of the hot melt adhesive, and improve heat resistance.

[0090] The softening point of the polypropylene wax (D) is 90°C or higher, 100°C or higher, 110°C or higher, 120°C or higher, 130°C or higher, 140°C or higher, or 150°C or higher, preferably 110°C or higher, more preferably 120°C or higher, and further preferably 130°C or higher. The softening point of the polypropylene wax (D) may be 220°C or lower, 210°C or lower, 190°C or lower, 180°C or lower, 170°C or lower, 160°C or lower, or 150°C or lower, preferably 190°C or lower, for example, 160°C or lower. From the viewpoint of better exerting the effects of the present disclosure, it is appropriate that the softening point of the polypropylene wax (D) is within the above range. The softening point of the polypropylene wax (D) can be measured in accordance with the ring & ball method, specifically, in accordance with JIS K6863: 1994 (softening point test method for hot melt adhesives). The softening point of the polypropylene wax (D) is not more than the above upper limit, and the melting temperature can be set low, which is preferred from the viewpoint of shortening the working time.

[0091] The weight average molecular weight of the polypropylene wax (D) may be 3,000 or more, 5,000 or more, or 7,000 or more, preferably 3,000 or more. The weight average molecular weight of the polypropylene wax (D) may be less than 40,000, less than 35,000, less than 30,000, less than 20,000, or less than 10,000, preferably less than 20,000. From the viewpoint of better exerting the effects of the present disclosure, it is appropriate that the weight average molecular weight is within the above range. The weight average molecular weight of the polypropylene wax (D) can be measured according to the method described in JIS K7252-1:2016 (Plastics - Size Exclusion Chromatography - Average Molecular Weight of Polymers and Method for Determination of Molecular Weight Distribution).

[0092] The polypropylene wax (D) may have repeating units other than repeating units derived from propylene, for example, repeating units derived from α-olefins. The polypropylene wax (D) may be a low molecular weight polyolefin, particularly a low molecular weight α-olefin polymer. The polypropylene wax (D) may be a homopolymer, a copolymer, a thermal decomposition product of a homopolymer, a thermal decomposition product of a copolymer, or a mixture thereof. The copolymer may be in the form of a random copolymer, a block copolymer, a graft copolymer, or the like.

[0093] Examples of repeating units other than repeating units derived from propylene contained in the polypropylene wax (D) include repeating units derived from ethylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, and 1-eicosene. These repeating units may be contained alone or in combination of two or more.

[0094] Among the repeating units constituting the polypropylene wax (D), the repeating units derived from propylene may account for 50 mol% or more, 60 mol% or more, 70 mol% or more, 80 mol% or more, or 90 mol% or more, and preferably 80 mol% or more.

[0095] Examples of representative commercial products of the polypropylene wax (D) include: VISCOL series products such as "VISCOL 660-P", "VISCOL 550-P", "VISCOL 440-P", and "VISCOL 330-P" manufactured by Sanyo Chemical Industries, Ltd.; HIWAX series products such as "HIWAX 100P", "HIWAX 200P", "HIWAX 400P", "HIWAX 800P", "HIWAX 410P", and "HIWAX 420P" manufactured by Mitsui Chemicals, Inc.; Licocene PP6102, "Licocene PP6502", and "Licocene PP660-P" manufactured by Clariant Chemicals, Inc. PP7502" and other Licocene series; China Essential Oil Company's trade names "L-C503NC", "L-C502NC", "L-C501NC", "L-C503N", "L-C502N", "L-C525N" and other LC series, etc. It should be noted that the polypropylene wax (D) can be used alone or in combination of two or more. Furthermore, waxes other than the polypropylene wax can also be blended within the range that does not impair the target properties.

[0096] [(E) Adhesive]

[0097] The hot melt adhesive composition of the present disclosure may contain a binder (E) (also referred to as component (E). The binder (E) can improve viscosity when melted.

[0098] The softening point of the adhesive (E) is 90°C or more, 100°C or more, 110°C or more, 120°C or more, 130°C or more, 140°C or more, or 150°C or more, preferably 110°C or more, more preferably 120°C or more, and further preferably 130°C or more. The softening point of the adhesive (E) may be 220°C or less, 210°C or less, 190°C or less, 180°C or less, 170°C or less, 160°C or less, or 150°C or less, preferably 190°C or less, for example, 160°C or less. From the viewpoint of better exerting the effects of the present disclosure, it is appropriate that the softening point of the adhesive (E) is within the above range. The softening point of the adhesive (E) can be measured according to the ring & ball method, specifically, according to the method described in JIS K 6863:1994 (softening point test method for hot melt adhesives). The softening point of the binder (E) is not more than the above upper limit, and the melting temperature can be set low, which is preferred from the viewpoint of shortening the working time.

[0099] Examples of the binder (E) include rosin resin, rosin ester, disproportionated rosin ester, hydrogenated rosin ester, polymerized rosin, aliphatic hydrocarbon resin, aliphatic aromatic copolymer resin, aromatic petroleum resin, hydrogenated petroleum resin, terpene resin, hydrogenated terpene resin, aromatic modified terpene resin, hydrogenated aromatic modified terpene resin, terpene phenolic resin, hydrogenated terpene phenolic resin, styrene resin, coumarone resin, indene resin, etc. Among them, from the viewpoint of compatibility with polyolefin, preferred examples include hydrogenated petroleum resin, terpene resin or terpene phenolic resin. It should be noted that the binder (E) is a substance different from other components such as polyolefin from the viewpoint of the presence or absence of intramolecular double bonds, intramolecular polar groups, intramolecular hydrocarbon groups, etc.

[0100] Examples of representative commercial products of the binder (E) include: ARKON series products manufactured by Arakawa Chemical Industries, Ltd. under the trade names “ARKON P-90”, “ARKON P-100”, “ARKON P-115”, “ARKON P-140”, “ARKON M-90”, “ARKON M-100”, “ARKON M-115”, and “ARKON M-135”; IMARV series products manufactured by Idemitsu Kosan Co., Ltd. under the trade names “IMARV S-100”, “IMARV S-110”, “IMARV P-100”, “IMARV P-125”, and “IMARV P-140”; T-REZ series products manufactured by ENEOS under the trade names “T-REZ HA103”, “T-REZ HA105”, “T-REZ HA125”, “T-REZ HB125”, and “T-REZ OP501”; and YS RESIN series products manufactured by Yasuhara Chemical Co., Ltd. under the trade name “YS RESIN YSRESIN series or YS POLYSTER series such as "YSRESIN PX1250", "YSRESIN PX1150", "YSRESIN PXI1000", "YSRESIN PX1150N", "YSRESIN TO125", "YSRESIN TO115", "YSRESIN TO105", "YS POLYSTER T160", "YS POLYSTER T145", "YSPOLYSTER T130", "YS POLYSTER T115", "YS POLYSTER T100", "YS POLYSTER UH115"; FTR series such as "FTR6100", "FTR6110", "FTR6125" manufactured by Mitsui Chemicals, Inc., etc. It should be noted that the binder (E) may be used alone or in combination of two or more. Furthermore, a binder having a softening point of less than 90°C may be blended within a range that does not impair the target physical properties.

[0101] [(F) Antioxidant]

[0102] The hot melt adhesive composition of the present disclosure may contain an antioxidant (F) (also referred to as component (F). Inclusion of an antioxidant (F) is preferred because thermal stability can be improved and the effects of the present disclosure can be more effectively exhibited.

[0103] Examples of the antioxidant (F) include hindered phenols, polyphenols, bisphenols, phosphoric acid esters, thioethers, hydrotalcites, benzimidazoles, and aromatic secondary amines.

[0104] Examples of representative commercially available antioxidants (F) include: Irganox series products manufactured by BASF under the trade names of “Irganox 1010”, “Irganox 1035”, “Irganox 1076”, “Irganox 1098”, “Irganox 1330”, “Irganox 245”, “Irganox 259”, “Irganox 3114”, “Irganox 565”, and “Irgafos 168”; and ADEKA STAB AO-20, ADEKA STAB AO-30, ADEKA STAB AO-40, ADEKA STAB AO-50, ADEKA STAB AO-60, ADEKA STAB AO-80, ADEKA STAB AO-330, ADEKA STAB PεP-8, ADEKA STAB PEP-36, ADEKA STAB PEP-37, ADEKA STAB PEP-48, ADEKA STAB PEP-59, ADEKA STAB PEP-60, ADEKA STAB PEP-70, ADEKA STAB PEP-81, ADEKA STAB PEP-82, ADEKA STAB PEP-83, ADEKA STAB PEP-84, ADEKA STAB PEP-85, ADEKA STAB PEP-86, ADEKA STAB PEP-87, ADEKA STAB PEP-88, ADEKA STAB PEP-89, ADEKA STAB PEP-80, ADEKA STAB PEP-81, ADEKA STAB PEP-82, ADEKA STAB PEP-83, ADEKA STAB PEP-86, ADEKA STAB PEP-87, ADEKA STAB PEP-88, ADEKA STAB PEP-89, ADEKA STAB PEP-80, ADEKA STAB PEP-83 HP-10", "ADEKA STAB 2112", "ADEKA STAB AO-412S" and other ADEKA STAB series. In addition, the antioxidant (F) may be used alone or in combination of two or more.

[0105] [(G) Inorganic filler]

[0106] The hot melt adhesive composition of the present disclosure may contain an inorganic filler (G) (also referred to as component (G)). By adding the inorganic filler (G), the adhesiveness, the sag property, the specific gravity, etc. can be adjusted.

[0107] Examples of the inorganic filler (G) include calcium carbonate (heavy calcium carbonate, surface untreated calcium carbonate, surface treated calcium carbonate (e.g., fatty acid treated calcium carbonate, etc.), needle-shaped crystalline calcium carbonate), silica (fumed silica, hydrophobic silica, precipitated silica, etc.), talc, mica (mica), clay, chrysotile, wollastonite, carbon black, graphite, balls (diatom balls (shirasu-balls oo ns), glass balls, silica balls, etc.), inorganic fibers (glass fibers, metal fibers, etc.), titanium oxide, aluminum oxide, aluminum borate, silicon carbide, silicon nitride, potassium titanate, magnesium borate, titanium diboride, aluminum flakes, aluminum powder, iron powder, etc. It should be noted that the inorganic filler (G) can be used alone or in combination of two or more.

[0108] [(H) Plasticizer]

[0109] The hot melt adhesive composition of the present disclosure may contain a plasticizer (H) (also referred to as component (H)). The plasticizer (H) is an oily substance such as a low molecular weight compound containing a chain alkyl group or an olefin oligomer. The plasticizer (H) can improve its coating properties and wettability to the adherend by reducing the viscosity of the hot melt adhesive.

[0110] The weight average molecular weight of the plasticizer (H) may be greater than 100, greater than 300, greater than 500, or greater than 1000. The weight average molecular weight of the plasticizer (H) may be less than 20,000, less than 16,000, less than 12,000, less than 5,000, or less than 3,000, preferably less than 12,000. From the viewpoint of better exerting the effects of the present disclosure, it is appropriate for the weight average molecular weight to be within the above range. The weight average molecular weight of the plasticizer (H) can be measured according to the method described in JIS K7252-1:2016 (Plastics - Average molecular weight of polymers by size exclusion chromatography and determination of molecular weight distribution).

[0111] Examples of the plasticizer (H) include liquid paraffin, process oil, phthalic acid plasticizer, butene oligomer, butadiene oligomer, liquid ethylene-propylene oligomer, liquid rubber, etc. From the viewpoint of compatibility, butene oligomer or liquid ethylene-propylene oligomer is preferred.

[0112] Examples of representative commercial products of the plasticizer (H) include: POLYBUTENE series such as "POLYBUTENE 0N", "POLYBUTENE 015N", "POLYBUTENE 3N", "POLYBUTENE 10N", "POLYBUTENE 30N", and "POLYBUTENE 200N" manufactured by NOF Corporation; and LUCANT series such as "LUCANT LX004", "LUCANT LX010", "LUCANT LX020", "LUCANT LX100", "LUCANT LX200", "LUCANT LX400", "LUCANT LX900Z", "LUCANT A-5515", and "LUCANT A-5260" manufactured by Mitsui Chemicals, Inc. It should be noted that the plasticizer (H) may be used alone or in combination of two or more.

[0113] [(I) Other ingredients]

[0114] In addition to the above, the hot melt adhesive composition of the present invention may also contain other components (I) (also referred to as component (I)) as needed. Examples of other components (I) include: colorants (e.g., red iron oxide (Bengala), titanium oxide, other coloring pigments, dyes, etc.); organic solvents (methanol, ethanol, isopropanol, butanol, acetone, methyl ethyl ketone, petroleum ether, ethyl acetate, tetrahydrofuran, n-hexane, heptane or isoparaffin high boiling point solvents, etc.); adhesives (silane coupling agents such as vinyltrimethoxysilane, vinyltriethoxysilane, aminosilane, mercaptosilane, epoxysilane, epoxy compounds such as glycidyl ether having a polyoxyalkylene skeleton, etc.); vulcanization accelerators (guanidines, aldehyde amines, aldehyde amines, thiazoles, sulfenamides, etc.). , thioureas, thiurams, dithiocarbamates, xanthates, etc.); vulcanization aids (long-chain fatty acids with more than 12 carbon atoms such as stearic acid, oleic acid, and palmitic acid; metal oxides such as zinc oxide, magnesium oxide, and lead oxide); antioxidants (hindered phenols, thiols, sulfides, dithiocarboxylates, thioureas, thiophosphates, thioaldehydes, etc.); ultraviolet absorbers and light stabilizers (benzotriazoles, hindered amines, etc.); thixotropic agents (colloidal silica, organic bentonite, fatty acid amides, hydrogenated castor oil, etc.); resins and polymer components other than the above (thermosetting resins, thermoplastic resins, etc.). These may be used alone or in combination of two or more.

[0115] The hot melt adhesive composition of the present disclosure may be a solvent-free type or may not contain a solvent.

[0116] The hot melt adhesive composition of the present disclosure may be non-reactive and may not contain reactive additives.

[0117] [composition]

[0118] The amount of component (A) based on 100 mass % of the hot-melt adhesive composition may be 2.5 mass % or more, 5 mass % or more, 7.5 mass % or more, 10 mass % or more, 12.5 mass % or more, or 15 mass % or more, and is preferably 5 mass % or more.

[0119] The amount of component (A) based on 100 mass % of the hot-melt adhesive composition may be 30 mass % or less, 25 mass % or less, 20 mass % or less, 15 mass % or less, 10 mass % or less, or 7.5 mass % or less, and is preferably 10 mass % or less.

[0120] Taking the hot-melt adhesive composition as 100 mass%, the amount of component (B) can be 2.5 mass% or more, 5 mass% or more, 7.5 mass% or more, 10 mass% or more, 12.5 mass% or more, 15 mass% or more, 17.5 mass% or more, 20 mass% or more, 22.5 mass% or more, or 25 mass% or more, preferably 15 mass% or more, and more preferably 20 mass% or more.

[0121] The amount of component (B) based on 100 mass % of the hot-melt adhesive composition may be 40 mass % or less, 35 mass % or less, 30 mass % or less, 25 mass % or less, 20 mass % or less, or 15 mass % or less, and is preferably 30 mass % or less.

[0122] Taking the hot-melt adhesive composition as 100 mass %, the amount of component (C) can be 2.5 mass % or more, 5 mass % or more, 7.5 mass % or more, 10 mass % or more, 12.5 mass % or more, or 15 mass % or more, preferably 5 mass % or more, and more preferably 7.5 mass % or more.

[0123] Taking the hot-melt adhesive composition as 100 mass %, the amount of component (C) can be 25 mass % or less, 20 mass % or less, 15 mass % or less, 12.5 mass % or less, 10 mass % or less, or 7.5 mass % or less, preferably 15 mass % or less, and more preferably 12.5 mass % or less.

[0124] Taking the hot-melt adhesive composition as 100 mass %, the amount of component (D) can be 10 mass % or more, 15 mass % or more, 20 mass % or more, 25 mass % or more, 30 mass % or more, 35 mass % or more, 40 mass % or more, 45 mass % or more, 50 mass % or more, and preferably 30 mass % or more.

[0125] Taking the hot-melt adhesive composition as 100 mass %, the amount of component (D) can be 75 mass % or less, 70 mass % or less, 65 mass % or less, 60 mass % or less, 55 mass % or less, 50 mass % or less, or 45 mass % or less, preferably 65 mass % or less, and more preferably 50 mass % or less.

[0126] Taking the hot-melt adhesive composition as 100 mass%, the amount of component (E) can be 2.5 mass% or more, 5 mass% or more, 7.5 mass% or more, 10 mass% or more, 12.5 mass% or more, 15 mass% or more, 17.5 mass% or more, 20 mass% or more, 22.5 mass% or more, or 25 mass% or more, preferably 10 mass% or more, and more preferably 15 mass% or more.

[0127] The amount of component (E) based on 100 mass % of the hot-melt adhesive composition may be 40 mass % or less, 35 mass % or less, 30 mass % or less, 25 mass % or less, 20 mass % or less, or 15 mass % or less, and is preferably 30 mass % or less.

[0128] The amount of component (F) based on 100 mass % of the hot-melt adhesive composition may be 0.01 mass % or more, 0.05 mass % or more, 0.1 mass % or more, 0.3 mass % or more, 0.5 mass % or more, 0.75 mass % or more, or 1 mass % or more, and is preferably 0.1 mass % or more.

[0129] The amount of component (F) based on 100 mass % of the hot-melt-adhesive composition may be 5 mass % or less, 4 mass % or less, 3 mass % or less, 2 mass % or less, or 1 mass % or less, and is preferably 3 mass % or less.

[0130] Taking the hot-melt adhesive composition as 100 mass %, the amount of component (G) can be 1 mass % or more, 2.5 mass % or more, 5 mass % or more, 7.5 mass % or more, 10 mass % or more, 12.5 mass % or more, or 15 mass % or more, preferably 2.5 mass % or more, and more preferably 5 mass % or more.

[0131] The amount of component (G) may be 30% by mass or less, 25% by mass or less, 20% by mass or less, 15% by mass or less, 10% by mass or less, or 5% by mass or less based on 100% by mass of the hot-melt-adhesive composition.

[0132] The amount of other components (I) in the hot-melt-adhesive composition of the present disclosure may be appropriately selected depending on each component.

[0133] The total amount of other components (I) may be 0.1% by mass or more, 0.2% by mass or more, 0.5% by mass or more, 1% by mass or more, 2.5% by mass or more, or 5% by mass or more based on 100% by mass of the hot-melt adhesive composition.

[0134] Taking the hot-melt adhesive composition as 100 mass %, the total amount of other components (I) may be 30 mass % or less, 25 mass % or less, 20 mass % or less, 15 mass % or less, 10 mass % or less, 7.5 mass % or less, or 5 mass % or less, 2.5 mass % or less, or 1 mass % or less, preferably 20 mass % or less, and more preferably 10 mass % or less.

[0135] Taking the hot-melt adhesive composition as 100 mass %, the amount of each component of other component (I) may be 0.01 mass % or more, 0.05 mass % or more, 0.1 mass % or more, 0.3 mass % or more, 0.5 mass % or more, 0.75 mass % or more, 1 mass % or more, or 2.5 mass % or more.

[0136] Moreover, based on 100 mass % of the hot-melt adhesive composition, the amount of each of the other components (I) may be 10 mass % or less, 7.5 mass % or less, 5 mass % or less, 2.5 mass % or less, or 1 mass % or less.

[0137] Taking the hot-melt adhesive composition as 100 mass%, the total amount of components (A) and (B) may be 5 mass% or more, 10 mass% or more, 15 mass% or more, 20 mass% or more, 25 mass% or more, 30 mass% or more, 35 mass% or more, 40 mass% or more, 45 mass% or more, or 50 mass% or more, preferably 20 mass% or more, and more preferably 30 mass% or more.

[0138] Taking the hot melt adhesive composition as 100 mass%, the total amount of components (A) and (B) may be 80 mass% or less, 70 mass% or less, 60 mass% or less, 50 mass% or less, 40 mass% or less, or 30 mass% or less, preferably 60 mass% or less. From the viewpoint of better exerting the effects of the present disclosure, it is appropriate that the total amount of components (A) and (B) is within the above range.

[0139] The amount of component (A) relative to 100 parts by mass of component (B) can be 15 parts by mass or more, 20 parts by mass or more, 25 parts by mass or more, 50 parts by mass or more, 75 parts by mass or more, or 100 parts by mass or more, preferably 15 parts by mass or more, more preferably 20 parts by mass or more, and even more preferably 25 parts by mass or more.

[0140] Relative to 100 parts by mass of the amount of component (B), the amount of component (A) may be 500 parts by mass or less, 450 parts by mass or less, 400 parts by mass or less, 350 parts by mass or less, 300 parts by mass or less, 200 parts by mass or less, 150 parts by mass or less, 100 parts by mass or less, 75 parts by mass or less, or 50 parts by mass or less, preferably 100 parts by mass or less, more preferably 75 parts by mass or less, and further preferably 50 parts by mass or less. From the viewpoint of better exerting the effect of the present disclosure, it is appropriate that the amount of component (A) is within the above range.

[0141] The amount of component (D) relative to 100 parts by mass of the total amount of components (A), (B) and (C) may exceed 60 parts by mass, and may be 65 parts by mass or more, 70 parts by mass or more, 80 parts by mass or more, 90 parts by mass or more, 100 parts by mass or more, 110 parts by mass or more, or 120 parts by mass or more, preferably 60 parts by mass or more, more preferably 80 parts by mass or more, and even more preferably 90 parts by mass or more.

[0142] Relative to the total amount of 100 parts by mass of components (A), (B) and (C), the amount of component (D) can be 300 parts by mass or less, 250 parts by mass or less, 200 parts by mass or less, 180 parts by mass or less, 150 parts by mass or less or 120 parts by mass or less, preferably 300 parts by mass or less, more preferably 250 parts by mass or less, and further preferably 180 parts by mass or less. From the viewpoint of better exerting the effect of the present disclosure, it is appropriate that the amount of component (D) is within the above range. By making the amount of component (D) above the above lower limit, the crystallinity of α-olefin (co)polymers (A) and (B) can be increased, the softening point of the hot melt adhesive can be increased, and the heat resistance can be improved. By making the amount of component (D) below the above upper limit, the crack resistance can be improved.

[0143] The amount of component (E) relative to 100 parts by mass of the total amount of components (A), (B) and (C) can be 10 parts by mass or more, 20 parts by mass or more, 30 parts by mass or more, 40 parts by mass or more, 50 parts by mass or more, or 60 parts by mass or more, preferably 20 parts by mass or more, and more preferably 40 parts by mass or more.

[0144] The amount of component (E) may be 150 parts by mass or less, 125 parts by mass or less, 100 parts by mass or less, 75 parts by mass or less, 50 parts by mass or less, or 30 parts by mass or less, preferably 100 parts by mass or less, and more preferably 75 parts by mass or less, relative to 100 parts by mass of the total amount of components (A), (B) and (C). From the viewpoint of better exerting the effects of the present disclosure, it is appropriate that the amount of component (E) is within the above range.

[0145] The amount of component (G) relative to 100 parts by mass of the total amount of components (A), (B) and (C) can be 5 parts by mass or more, 10 parts by mass or more, 15 parts by mass or more, 20 parts by mass or more, 25 parts by mass or more, or 30 parts by mass or more, preferably 10 parts by mass or more, and more preferably 20 parts by mass or more.

[0146] The amount of component (G) may be 75 parts by mass or less, 60 parts by mass or less, 50 parts by mass or less, 40 parts by mass or less, 30 parts by mass or less, or 20 parts by mass or less, preferably 60 parts by mass or less, and more preferably 40 parts by mass or less, relative to 100 parts by mass of the total amount of components (A), (B) and (C). From the viewpoint of better exerting the effects of the present disclosure, it is appropriate that the amount of component (G) is within the above range.

[0147] [physical properties]

[0148] The hot melt adhesive composition of the present disclosure may have a melt viscosity of 5,000 mPa·s or more, 7,000 mPa·s or more, 10,000 mPa·s or more, 12,000 mPa·s or more, 15.000 mPa·s or more, 20,000 mPa·s or more, or 25,000 mPa·s or more, preferably 7,000 mPa·s or more, and more preferably 10,000 mPa·s or more, at 180°C, which is a normal coating temperature of the hot melt adhesive.

[0149] The hot melt adhesive composition of the present disclosure may have a melt viscosity of 200,000 mPa·s or less, 150,000 mPa·s or less, 100,000 mPa·s or less, 50,000 mPa·s or less, 30,000 mPa·s or less, or 20,000 mPa·s or less, preferably 100,000 mPa·s or less, and more preferably 50,000 mPa·s or less at 180° C., which is a normal coating temperature of the hot melt adhesive.

[0150] If the melt viscosity is within the above range, it is not easy to produce droplets or coating marks when applied to the adherend, which is preferred. The above melt viscosity is a value measured using a parallel plate rheometer (MCR102e manufactured by Anton Paar) at a temperature of 180°C, a shear rate of 4.3 sec-1, and a clearance of 0.5 mm.

[0151] <Method for producing hot-melt adhesive composition>

[0152] The hot melt adhesive composition of the present disclosure can be produced by mixing components (A) to (D) while appropriately heating them. The hot melt adhesive composition of the present disclosure can be produced, for example, by adding components (A) to (D) together with components (E) to (F) and / or other components as needed, adding each component together or sequentially, and mixing them while appropriately heating them using a heating mixer.

[0153] The method for producing the hot melt adhesive of the present invention comprises the following steps:

[0154] Preparing: an α-olefin (co)polymer (A) having a Shore A hardness of 80 or more produced using a single-site catalyst, an α-olefin (co)polymer (B) having a Shore A hardness of less than 80 produced using a single-site catalyst, an ethylene-polar group-containing monomer copolymer (C), and a polypropylene wax (D); and

[0155] Relative to 100 parts by mass of the total amount of the above-mentioned α-olefin (co)polymer (A), the above-mentioned α-olefin (co)polymer (B) and the ethylene-polar group-containing monomer copolymer (C), 60 parts by mass or more and 300 parts by mass or less of the above-mentioned polypropylene wax (D) are melt-mixed.

[0156] <Adhesive body and method for producing the same>

[0157] The adhesive body of the present disclosure includes a first substrate and a second substrate, and the second substrate is bonded to the first substrate via a hot-melt adhesive layer formed of a hot-melt adhesive composition.

[0158] The method for producing an adhesive body of the present disclosure includes the steps of applying the hot-melt adhesive composition of the present disclosure on one surface of a first substrate to form a hot-melt adhesive layer (coating step); and bonding the first substrate and a second substrate via the hot-melt adhesive layer (bonding step).

[0159] Furthermore, the method for producing an adhesive body in the present disclosure may include a step of crystallizing the hot-melt adhesive layer (curing step).

[0160] [Base material]

[0161] There is no particular restriction on the substrates used as the first substrate and the second substrate, and examples thereof include: wood materials; plastic materials such as polyolefins, polyvinyl chloride, polyurethane, polyester, epoxy resin, etc.; foams of the above plastic materials; rubber materials such as natural rubber and synthetic rubber; metal materials such as aluminum, iron, stainless steel, etc.; materials made of inorganic materials such as ceramics, etc. There is no particular restriction on the shape of each substrate, and for example, it can be a sheet, foil, plate, or molded body. In addition, each substrate can be composed of only one material, or it can be composed of two or more materials. The material of the surface of the substrate provided with the adhesive layer is preferably non-metal, more preferably a resin as described above, and further preferably a polyolefin represented in particular by polypropylene.

[0162] [Coating process]

[0163] In the coating process, various hot melt adhesive coaters can be used as a method for coating the substrate, and methods such as using a spray gun, a comma coater, a die coater, and a roller coater can be cited. When coating the substrate, it can usually be heated at a temperature of 140°C to 200°C to melt it, and coated in a molten state. After coating on a release film or release paper, it can be thermally transferred to other substrates for use. By cooling after coating, the hot melt adhesive layer can be solidified on the substrate. The pre-coated substrate (substrate containing an adhesive layer) obtained after the coating process can be directly supplied to the next molding process, or it can be stored and then supplied to the next process.

[0164] [Bonding process]

[0165] In the bonding process, the hot melt adhesive layer can be heated and activated to melt again as needed. As a means of heating and activation, there are methods such as heating, ultrasonic waves, high frequency, microwaves, etc., which are not particularly limited. Reactivation is preferably carried out before the pre-coated substrate and the second substrate are crimped. The crimping of the pre-coated substrate and the second substrate is carried out before the hot melt adhesive composition layer is solidified. There is no particular limitation on the crimping method, and for example, crimping molding method, vacuum forming method, etc. can be cited. The second substrate may be heated or not. In addition, if the hot melt adhesive composition layer is in a reactivated state, it may not be heated during crimping, but it may also be heated while pressurizing as needed.

[0166] The temperature for heating activation is preferably 100° C. to 200° C., for example, 100° C. to 180° C., and more preferably 120° C. to 160° C., based on the surface temperature of the hot-melt adhesive layer. The pressure during the pressure bonding involving the bonding of the first substrate and the second substrate can be 0.01 MPa to 0.50 MPa, preferably 0.01 MPa to 0.20 MPa, and more preferably 0.01 MPa to 0.10 MPa. The time during the pressure bonding can be, for example, 1 second to 300 seconds, preferably 1 second to 60 seconds, and more preferably 10 seconds to 30 seconds.

[0167] <Automobile interior material and method for producing the same>

[0168] [Automotive interior materials]

[0169] The automobile interior material disclosed herein includes an automobile interior molded article and an automobile interior skin material (hereinafter also referred to as "skin material"), wherein the automobile interior skin material is bonded to the automobile interior molded article via a hot melt adhesive layer formed from the hot melt adhesive composition disclosed herein. The skin material may be a skin material derived from a skin material containing a hot melt adhesive layer (pre-coated skin material). Examples of automobile interior materials include door trims, instrument panels, ceiling materials, rear trays, pillars, and the like.

[0170] As for the material of the molded article for automobile interior, there is no particular limitation as long as it is a material used for automobile interior materials, and examples thereof include: wood materials such as paper and wood; plastic materials such as polyolefins (polypropylene, polyethylene, ethylene-propylene copolymers, etc.), polyvinyl chloride, polyurethane, polyester, epoxy resin, nylon, polyester, polycarbonate, polyurethane, acrylic, ABS, PCABS, etc.; rubber materials such as natural rubber and synthetic rubber; metal materials such as aluminum, iron, stainless steel, etc.; inorganic materials such as ceramics, etc. The molded article for automobile interior can be composed of only one material or two or more materials. The material of the surface of the molded article for automobile interior provided with the adhesive layer is preferably the above-mentioned non-metallic molded article material for automobile interior, more preferably the above-mentioned molded article material for automobile interior made of resin, and further preferably a polyolefin represented by polypropylene.

[0171] The skin material is not particularly limited as long as it is a material used for automobile interior materials, and examples thereof include: plastic sheets such as polyolefins, soft polyvinyl chloride, and polyurethane; foams of the above plastics; rubber sheets such as natural rubber and synthetic rubber; textile materials such as woven fabrics and non-woven fabrics; metal foils such as aluminum, etc. The skin material may consist of only one layer, or may include two or more layers of the same material or different materials. As a skin material comprising two or more layers, examples thereof include: a sheet formed by laminating one or more layers of the above plastic foam on one or more layers of the above plastic sheet, rubber sheet, textile material, metal foil, etc. As such a laminated sheet, examples thereof include: soft polyvinyl chloride with polyolefin foam, olefin thermoplastic elastomer with polyolefin foam, fabric with polyurethane foam, etc. The material of the surface of the skin material provided with an adhesive layer is preferably a non-metallic material of the above skin material, more preferably a resin material of the above skin material, and further preferably a polyolefin represented by polypropylene.

[0172] [Manufacturing method of automobile interior material]

[0173] In the manufacturing method of the automobile interior material disclosed in the present invention, in the manufacturing method of the above-mentioned adhesive body, the adhesive body can be an automobile interior material, the first substrate can be a skin material, and the second substrate can be a molded product for automobile interior. Conversely, the following situation can also be adopted: the adhesive body is an automobile interior material, the first substrate is a molded product for automobile interior, and the second substrate is a skin material.

[0174] An example of a method for manufacturing an automotive interior material may include the following steps: applying the hot melt adhesive composition of the present invention to the back side of a skin material (e.g., a foaming layer of the skin material) to obtain a skin material (pre-coated skin material) containing a hot melt adhesive layer; reactivating the obtained pre-coated skin material with a far-infrared heater, etc., so that the hot melt adhesive layer is melted, and then the skin material is crimped to a molded article for automotive interior via the hot melt adhesive layer. Furthermore, a curing step for crystallizing the hot melt adhesive layer may also be included. It should be noted that in the step of crimping with a substrate, when heating and crimping can be performed, it is sometimes not necessary to reactivate using a far-infrared heater, etc. It should be noted that the back side of the skin material refers to the side opposite to the molded article for automotive interior when the skin material is bonded to the molded article for automotive interior.

[0175] [Example]

[0176] Hereinafter, the present disclosure will be described in more detail with reference to Examples and Comparative Examples, but the present disclosure is not limited to these Examples and Comparative Examples.

[0177] Components used in Examples and Comparative Examples are shown below.

[0178] (A) α-olefin (co)polymer having a Shore A hardness of 80 or more produced using a single-site catalyst

[0179] A-1: WINTEC WSX03 manufactured by Japan Polypro (melting point 125°C, Shore A hardness 98, polypropylene produced using a single-site catalyst)

[0180] A-2: VERSIFY 3000 manufactured by Dow Chemical (melting point 108°C, Shore A hardness 96, propylene-ethylene copolymer produced using a single-site catalyst)

[0181] A-3: TAFMERXM-7090 manufactured by Mitsui Chemicals (melting point 98°C, Shore A hardness 97, propylene-butene copolymer produced using a single-site catalyst)

[0182] A-4: VISTAMAXX 3588FL manufactured by Exxon Mobil (melting point 108°C, Shore A hardness 94, ethylene content 4 wt%, propylene-ethylene copolymer produced using a single-site catalyst)

[0183] A-5: VISTAMAXX 3980FL manufactured by Exxon Mobil (melting point 78°C, Shore A hardness 84, ethylene content 9 wt%, propylene-ethylene copolymer produced using a single-site catalyst)

[0184] A-6: L-MODU S901 manufactured by Idemitsu Kosan Co., Ltd. (melting point 80°C, Shore A hardness 84, polypropylene produced using a single-site catalyst)

[0185] (B) α-olefin (co)polymers having a Shore A hardness of less than 80, produced using a single-site catalyst

[0186] B-1: TAFMER PN-2070 manufactured by Mitsui Chemicals (melting point 140°C, Shore A hardness 75, propylene polymer produced using a single-site catalyst)

[0187] B-2: VISTAMAXX 6502 manufactured by Exxon Mobil (melting point 63°C, Vicat softening temperature 51°C, Shore A hardness 71, ethylene content 13 wt%, propylene-ethylene copolymer produced using a single-site catalyst)

[0188] B-3: VISTAMAXX 6202 manufactured by Exxon Mobil (melting point 60°C, Vicat softening point 45°C, Shore A hardness 64, ethylene content 15 wt%, propylene-ethylene copolymer produced using a single-site catalyst)

[0189] (C) Ethylene-Polar Group-Containing Monomer Copolymer

[0190] C-1: Ultrathene 722 manufactured by Tosoh Corporation (melting point 65°C, Shore A hardness 69, vinyl acetate content 28 wt%, ethylene-vinyl acetate copolymer)

[0191] C-2: NUC-6070 manufactured by ENEOS NUC (melting point 87°C, Shore A hardness 79, ethyl acrylate content 25 wt%, ethylene-ethyl acrylate copolymer)

[0192] (X) α-olefin (co)polymers produced using multi-site catalysts

[0193] X-1: VESTOPLAST 792 manufactured by Evonic (softening point 108°C, Shore A hardness 70, weight average molecular weight 118,000, amorphous polyolefin produced using a multi-site catalyst)

[0194] (D) Polypropylene wax

[0195] D-1: VISCOL 660-P manufactured by Sanyo Chemical Industries, Ltd. (softening point 145°C, weight average molecular weight 10,000, polypropylene wax)

[0196] D'-2: SANWAX 171-P manufactured by Sanyo Chemical Industries, Ltd. (softening point 107°C, weight average molecular weight 10,000, polyethylene wax)

[0197] (E) Adhesive

[0198] · E-1: Arakawa Chemical Industries, Ltd. ARKON P115 (softening point 115°C, hydrogenated petroleum)

[0199] · E-2: YS RESIN PX1150 manufactured by Yasuhara Chemical1 (softening point 115°C, terpene)

[0200] · E-3: YS POLYSTER UH115 manufactured by Yasuhara Chemical Co., Ltd. (softening point 115°C, hydrogenated terpene phenol)

[0201] (F) Additives (antioxidants)

[0202] F-1: Irganox 1010 manufactured by BASF (melting point 110°C, hindered phenol)

[0203] F-2: Irgafos 168 manufactured by BASF (melting point 183°C, phosphorus type)

[0204] <Examples 1 to 13 and Comparative Examples 1 to 7>

[0205] The components shown in Tables 1 to 3 below were melt-mixed at 180° C. in parts by mass using a kneader equipped with a heat medium jacket (Kneader Hibismix 2P-1 manufactured by Primix) to obtain hot melt adhesive compositions of Examples 1 to 13 and Comparative Examples 1 to 7.

[0206] The melt viscosity of the hot melt adhesive compositions of Examples 1 to 13 and Comparative Examples 1 to 7 was measured. Furthermore, crack resistance and blocking resistance were evaluated. In addition, samples for bonding tests were prepared and initial creep, bonding strength, and heat creep resistance were evaluated. The evaluation method or measurement method, etc. are shown below.

[0207] [Melt viscosity]

[0208] A parallel plate rheometer (MCR102e manufactured by Anton Paar) was used at a temperature of 180°C and a shear rate of 4.3 seconds. -1 The results are shown in Tables 1 to 3.

[0209] [Crack resistance]

[0210] The adhesive was coated with a roll coater at 180°C to give an adhesive layer of 100 g / m 2 The adhesive was applied to the foam layer surface of the skin material (artificial leather / polypropylene foam layer formed of thermoplastic polyolefin, total thickness 4 mm). Next, one day after the adhesive was applied, the skin material was curled in an environment of 23°C so that the adhesive layer was on the outside. Next, the adhesive layer was visually observed for cracks and evaluated. The results are shown in Tables 1 to 3.

[0211] ○: No cracks

[0212] ×: Cracked

[0213] [Blocking resistance (and component migration resistance)]

[0214] The adhesive was coated with a roll coater at 180°C to give an adhesive layer of 100 g / m 2 The adhesive was applied to the surface of the foam layer of the skin material (artificial leather / polypropylene foam layer molded with thermoplastic polyolefin, with a total thickness of 4 mm). Next, within 30 minutes after the adhesive was applied, 5 sheets of the skin material were stacked, a load of 1.28 kPa was applied using a glass plate and a weight, and the skin material was left to stand in an oven at 40°C for 3 days. Next, the stacked skin material was taken out of the oven, and the skin materials were peeled off from each other by hand. The surfaces were visually observed to evaluate whether there was adhesion between the skin materials and whether there was component migration. The results are shown in Tables 1 to 3.

[0215] ○: No adhesion or component migration

[0216] ×: Any of adhesion and component migration exists

[0217] [Preparation of Sample 1 for Adhesion Test]

[0218] The adhesive was coated with a roll coater at 180°C to give an adhesive layer of 100 g / m 2 The adhesive was applied to the foam layer surface of the skin material (artificial leather / polypropylene foam layer formed of thermoplastic polyolefin, total thickness 4 mm). Next, within 1 day after the adhesive was applied, the skin material was heated to 170°C or higher with a far-infrared heater, and immediately overlapped with a PP plate (a flat plate formed of polypropylene, thickness 2 mm), and compacted at 0.1 MPa for 15 seconds to obtain a laminate (sample 1 for bonding test).

[0219] [Initial creep]

[0220] After obtaining the laminate (adhesion test sample 1), a load of 200 g / 25 mm was applied in a 90-degree angle direction in an atmosphere at 60°C, and the peel length (mm) after 5 minutes was measured. The results are shown in Tables 1 to 3.

[0221] [Adhesion strength]

[0222] After curing the laminate (adhesion test sample 1) at 25°C for 24 hours, the peel strength (N / 25mm) at 180 degrees was measured. The PP plate was fixed with a clamp and the surface material was peeled off by stretching. The measurement was performed at a peeling speed of 200 mm / min. Furthermore, the state of the surface after peeling was observed by visual inspection. The results are shown in Tables 1 to 3.

[0223] AF: Interface failure on the substrate side

[0224] MB: Material destruction of the skin material

[0225] CF: Cohesive failure of adhesive

[0226] The number after the damage state indicates the proportion of the damage state.

[0227] [Heat creep resistance]

[0228] After the laminate (adhesion test sample 1) was cured at 25°C for 24 hours, a load of 200 g / 25 mm was applied in an atmosphere of 80°C in a 90-degree angle direction, and the peeling length (mm) after 24 hours was measured. Furthermore, the state of the surface after peeling was visually observed. The results are shown in Tables 1 to 3.

[0229] AF: Interface failure on the substrate side

[0230] MB: Material destruction of the skin material

[0231] CF: Cohesive failure of adhesive

[0232] The number after the damage state indicates the proportion of the damage state.

[0233] [Table 1]

[0234]

[0235] [Table 2]

[0236]

[0237] [Table 3]

[0238]

[0239] The hot-melt adhesive compositions of Examples 1 to 13 exhibited good adhesiveness, heat resistance, crack resistance, and blocking resistance.

[0240] On the other hand, the hot-melt adhesive compositions of Comparative Examples 1 to 7 were insufficient in any of adhesiveness, heat resistance, crack resistance, and blocking resistance.

[0241] Since the hot-melt adhesive compositions of Comparative Examples 1 and 2 used the amorphous polyolefin (X) produced using a multisite catalyst instead of the component (B), the blocking resistance, thermal creep resistance, etc. were insufficient.

[0242] Since the hot-melt-adhesive composition of Comparative Example 3 did not contain the component (A), its blocking resistance and thermal creep resistance were insufficient.

[0243] Since the hot-melt-adhesive composition of Comparative Example 4 did not contain the component (B), the crack resistance was insufficient.

[0244] Since the hot-melt-adhesive composition of Comparative Example 5 did not contain the component (C), the blocking resistance was insufficient.

[0245] In the hot-melt adhesive composition of Comparative Example 6, since polyethylene wax was used instead of the polypropylene wax (D), the heat creep resistance was reduced.

[0246] The hot melt adhesive of Comparative Example 7 had an insufficient content of the polypropylene wax (D), poor compatibility, and insufficient crack resistance.

[0247] Industrial Applicability

[0248] The hot melt adhesive composition disclosed in the present invention can be used as a solvent-free adhesive without VOC emission, and has excellent adhesion and heat resistance to resin substrates, especially polyolefin substrates. In addition, when preparing pre-coated surface materials, it is excellent in blocking resistance and component migration resistance during stacking and storage, and excellent in crack resistance during transportation, so it can be suitably used as an adhesive for automobile interior.

Claims

1. A hot melt adhesive composition, characterized in that Include: An α-olefin (co)polymer (A) having a Shore A hardness of 80 or more produced using a single-site catalyst; α-olefin (co)polymers (B) having a Shore A hardness of less than 80 produced using a single-site catalyst; Ethylene-polar group-containing monomer copolymer (C); as well as Polypropylene wax (D); The polypropylene wax (D) is contained in an amount of more than 60 parts by mass and less than 300 parts by mass relative to 100 parts by mass of the total amount of the α-olefin (co)polymer (A), the α-olefin (co)polymer (B) and the ethylene-polar group-containing monomer copolymer (C).

2. The hot-melt adhesive composition according to claim 1, wherein Said α The α-olefin (co)polymer (A) comprises at least one selected from the group consisting of polypropylene, ethylene-propylene copolymers, and propylene-butene copolymers.

3. The hot-melt adhesive composition according to claim 1, wherein A part of the copolymerization component of the α-olefin (co)polymer (B) contains a repeating unit derived from propylene.

4. The hot-melt adhesive composition according to claim 1, wherein The ethylene-polar group-containing monomer copolymer (C) includes at least one selected from the group consisting of ethylene-vinyl acetate copolymers and ethylene-ethyl acrylate copolymers.

5. The hot-melt adhesive composition according to claim 1, wherein The softening point of the polypropylene wax (D) is 90° C. or higher.

6. The hot-melt adhesive composition according to claim 1, wherein Contains a binder (E).

7. The hot-melt adhesive composition according to claim 6, wherein The binder (E) includes at least one selected from the group consisting of hydrogenated petroleum resins, terpene resins, and hydrogenated terpene phenolic resins.

8. The hot-melt adhesive composition according to claim 1, wherein Contains antioxidant (F).

9. The hot-melt adhesive composition according to claim 1, wherein The hot-melt adhesive composition has a melt viscosity at 180° C. of 10,000 mPa·s or more and 50,000 mPa·s or less.

10. The hot-melt adhesive composition according to claim 1, which is used for automobile interior materials.

11. A pre-coated surface material for automobile interior, characterized in that: The invention comprises: a surface material for automobile interior, and a hot-melt adhesive layer formed of the hot-melt adhesive composition according to any one of claims 1 to 10 on the back surface of the surface material for automobile interior.

12. An automobile interior material, characterized in that: The invention comprises: a molded article for automobile interior, and the pre-coat surface material for automobile interior according to claim 11, wherein the pre-coat surface material for automobile interior is bonded to the molded article for automobile via the hot-melt adhesive layer.

13. A method for producing an adhesive body, wherein: The adhesive body comprises a first substrate and a second substrate, wherein the second substrate is bonded to the first substrate via a hot-melt adhesive layer formed from the hot-melt adhesive composition according to any one of claims 1 to 10. The method for producing an adhesive body includes a step of bringing a mold into contact with the hot-melt adhesive composition.

14. A method for producing a hot melt adhesive composition, characterized in that: include: Preparation: an α-olefin (co)polymer (A) having a Shore A hardness of 80 or more produced using a single-site catalyst; an α-olefin (co)polymer (B) having a Shore A hardness of less than 80 produced using a single-site catalyst; an ethylene-polar group-containing monomer copolymer (C); and a polypropylene wax (D); Relative to 100 parts by weight of the total amount of the α-olefin (co)polymer (A), the α-olefin (co)polymer (B) and the ethylene-polar group-containing monomer copolymer (C), 60 parts by weight or more and 300 parts by weight or less of the polypropylene wax (D) are melt-mixed.

Citation Information

Patent Citations

  • Precoated surface material for vehicular interior material and manufacturing method of vehicular interior material

    JP2004284575A